If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -23b = 35b Solving -23b = 35b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-35b' to each side of the equation. -23b + -35b = 35b + -35b Combine like terms: -23b + -35b = -58b -58b = 35b + -35b Combine like terms: 35b + -35b = 0 -58b = 0 Divide each side by '-58'. b = 0 Simplifying b = 0
| .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 | | (24)5= | | =7x+4(x+5) | | 4(x-6)+4=6x-8 | | 2r^2+18r+33=0 | | 2x+8=63 | | log(5x+70)=2 | | -55=3x+7x+5 | | =3(x+2)+5x | | 2(x-7)-1=-5(6-x) | | -1+x+x=13 | | 2(x+3)-3x+8=6(x-5)+2 | | 6x+1=-7 | | =3(x+2)+5z | | 0-4(-2)=0 | | (3m+m)*2=102 | | 18x-(12x+7)=5 | | -2p+-10+8= | | 10(x-3)=-5(x-6) | | 25x+3=5x+8 | | =b+a+2b+2a+a+1 | | 7+2k+5k+9= | | 4(3-x)=4 | | w^2+6=4w | | 10-6x-7-4x=5 | | 3x-9+6x=45 | | -4(y-7)=2(y+3)-4y+12 | | =24+6a+b+3a+b+3a |